Motivation And Capacity in Entrepreneurship: Are They Enough? (An Insight from Entrepreneur-Self-Test for Student at Politeknik eLBajo Commodus) - Marius Yosef Seran; Andy Iwan Iswanto; Fitri Ciptosari; Gregorius Antariksa Berybe (JURNAL AKADEMISI VOKASI, 2025)
This study explores the relationship between motivation and capacity, based on entrepreneurial self-test, as predictors of entrepreneurial potential among vocational students at Politeknik eLBajo Commodus. With the growing emphasis on entrepreneurship education in Indonesia, this research investigates whether motivation as an internal drive and capacity as a enabling factors are sufficient to foster entrepreneurial readiness. Using a quantitative explanatory design, data were collected through an Entrepreneur-Self-Test consisting of 27 indicators, and analyzed using JASP for descriptive statistics, reliability, correlation, and regression analysis. The findings reveal that while both motivation and capacity significantly influence entrepreneurial potential, capacity exhibits a stronger predictive power. The study concludes that motivation and capacity are necessary but not entirely sufficient for predicting entrepreneurial potential. Therefore, entrepreneurship education must integrate contextual skills and experiential learning to bridge mindset and execution. These insights contribute to the ongoing refinement of entrepreneurship class and curriculum, for broader inclusion of environmental and structural factors in student development strategies.